Local Self-Governance a Right Platform for Empowering Rural Women - Tigga, Adline Shanta (Indian Journal of Extension Education, 2021)
Panchayat Raj Institutions (PRI) is beginning to transform the process and priorities of local Government inÂ India as well as the women also have been brought into politics. Women representation in the Panchayati Raj system is a unique experiment which translates the idea of empowerment of women in reality. The process ofÂ challenging the existing power relation and gaining great control over the sources of power may be termed as empowerment. At the same time empowerment is an active, multidimensional process, which enable women toÂ realize their full identity and powers in all spheres of life. It is not a commodity to be transmitted nor can it be given away, power has to be required and once acquired it needs to be exercised, sustained and preserved. Empowerment is a process of awareness and capacity building leading to greater participation decision makingÂ and transformative action. This paper is an attempt to know extent of empowerment of panchayat women. The study was carried out in Pusa Block of Samastipur district in Bihar. In order to have a clear understanding of theÂ extent of women empowerment through local self governance, the study included both the positional women leader of gram panchayats of Pusa block and reputational women leader of this institution. The data obtainedwere quantified and put to statistical analysis for drawing meaningful conclusions. This paper concluded that there was an overall positive impact of increased participation of women in Gram Panchayats.